2019
DOI: 10.3390/cells8060628
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adipose Tissue in the Pathogenesis and Therapeutic Outcomes of Inflammatory Bowel Disease

Abstract: Though historically regarded as an inert energy store, adipose tissue is a complex endocrine organ, which is increasingly implicated in the pathogenesis of inflammatory bowel disease (IBD). Accumulating evidence points to visceral adipose tissue and specifically to its mesenteric component, or “creeping fat” as impacting on the disease course through its immunomodulatory properties. On the one hand, mesenteric fat acts as a physical barrier to inflammation and is involved in controlling host immune response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 142 publications
(172 reference statements)
1
50
0
Order By: Relevance
“…One retrospective review suggested that obese patients may have higher rates of perineal disease [ 25 ]; other studies found no differences in disease distribution or behavior for CD or UC patients [ 9 , 26 ]. These inconsistencies may be related to significant limitations of BMI as a biomarker of adiposity, as it is unable to differentiate between subcutaneous and visceral adipose tissue [ 27 ].…”
Section: Obesity and Ibdmentioning
confidence: 99%
See 2 more Smart Citations
“…One retrospective review suggested that obese patients may have higher rates of perineal disease [ 25 ]; other studies found no differences in disease distribution or behavior for CD or UC patients [ 9 , 26 ]. These inconsistencies may be related to significant limitations of BMI as a biomarker of adiposity, as it is unable to differentiate between subcutaneous and visceral adipose tissue [ 27 ].…”
Section: Obesity and Ibdmentioning
confidence: 99%
“…Adipose tissue is distributed in two main compartments, subcutaneous and visceral—see Figure 1 [ 27 , 34 ]. Exact differentiation of subcutaneous and visceral adipose tissue (VAT) is possible by abdominal magnetic resonance imaging or computed tomography used to measure the visceral fat area and subcutaneous fat area [ 15 , 35 ].…”
Section: Adipose Tissue As An Active Endocrine Organ Visceral Adipose Tissue and Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact that MAT is composed, in addition to adipocytes, of macrophages, after induction of monocyte chemoattractant protein-1 (MCP-1) expression, tissue infiltration by macrophages occurs. As a consequence, it may determine the severity of the disease and be a significant factor in pathogenesis [ 44 , 45 , 46 , 47 ]. More and more researchers draw attention to the link between leptin and IBD.…”
Section: Influence Of Obesity On the Course Of Ibdmentioning
confidence: 99%
“…Evaluating the impact of anti-TNFα therapy on anthropometric parameter changes in patients with IBD is of particular importance as the increase in lean mass is beneficial (muscle representing the protein reserves of the body and contributing to improved immune function). This is especially true in patients with aggressive IBD in which lower BMI values may result from malnutrition accompanied with severe inflammation [ 7 ]. Nevertheless, about 15–40% of patients with IBD are obese, and an additional 20–40% are overweight [ 9 13 ], so the potential involvement of adipose tissue in intestinal inflammation and therapeutic outcomes has gained increasing attention [ 10 ].…”
Section: Introductionmentioning
confidence: 99%